2007
DOI: 10.1177/016264340702200203
|View full text |Cite
|
Sign up to set email alerts
|

Developing Reflective Thought in Preservice Educators: Utilizing Role-Plays and Digital Video

Abstract: This study was designed to investigate the role of video in the growth of written reflective responses between two groups of preservice teachers. Fifty-four students enrolled in four sections of a required special education course that focused on family-professional collaboration participated. Subjects included candidates seeking general and special education certification and a teaching endorsement in special education. Participants were divided into two groups. Group 1 students participated in three role-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 8 publications
0
40
0
Order By: Relevance
“…For teachers, reflection involves the ability to evaluate one's teaching performance and make appropriate changes based on that to improve their teaching practice. Similar to classroom management skills, preservice teachers require intensive instruction to develop reflective practices in teaching (Robinson & Kelley, 2007).…”
Section: Possible Reasons For Disagreements Between the Quantitativementioning
confidence: 99%
“…For teachers, reflection involves the ability to evaluate one's teaching performance and make appropriate changes based on that to improve their teaching practice. Similar to classroom management skills, preservice teachers require intensive instruction to develop reflective practices in teaching (Robinson & Kelley, 2007).…”
Section: Possible Reasons For Disagreements Between the Quantitativementioning
confidence: 99%
“…Researchers such as Freese (1999), Robinson and Kelley (2007), and Sherin and van Es, (2005) consider that videos taken during lessons in teaching practice are trustworthy data for student teachers to make a post-lesson self reflection that is grounded in the actual records rather than uncertain recollections. The studies by these researchers also find that student teachers show significant growth in the levels of reflective thoughts about their teaching work, under a guiding framework for self reflection, after browsing video recordings of lessons in teaching practice.…”
Section: Background To the Studymentioning
confidence: 99%
“…The use of web enabled, video based systems, which make the production, transition and retrieval of video data executable through the use of virtualisation and remote access software for delivering applications over a network and the Internet, can support student teachers to gain a valuable, learner centred experience in reflective activities for self evaluation of teaching performance (Jonassen, Davidson, Collins, Campbell & Haag, 1995;Freese, 1999;Robinson & Kelley, 2007;Schauble, Raghavan & Glaser, 1993). With the provision of a template for self reflection on a dimensional basis, student teachers can reflect purposefully on their teaching performance after each lesson in teaching practice by browsing the corresponding video clips (see Figure 1).…”
Section: Background To the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, all situated performances involve role-play, but not all role-plays are situated performances. A recent study by Robinson and Kelley (2007) found that groups made significant gains in engaging in a higher level of dialogic reflection when they not only performed role-plays, but continually reviewed their role-plays using a streaming video server. There is also evidence that participants remember the learning derived from face-to-face roleplay after they have forgotten much of the learning they attained in other ways (Bell, 2001;Gredler, 1994;Van Ment, 1999).…”
Section: Theoretical Framework: Why Use Situatedmentioning
confidence: 99%